Nicotinamide-riboside shifts the differentiation of human primary white adipocytes to beige adipocytes impacting substrate preference and uncoupling respiration through SIRT1 activation and mitochondria-derived reactive species production - Nagy, Lilla; Rauch, Boglárka; Szerafin, Tamás; Uray, Karen; Tóth, Attila; Bai, Péter (Frontiers in Cell and Developmental Biology, 2022)
Beige adipocytes play key roles in organismal energy and metabolic balance. In this study, we assessed whether the supplementation of human white adipocytes, differentiated from human adipose tissue-derived stem cells, with nicotinamide riboside (NR), a potent NAD + precursor, can shift differentiation to beige adipocytes (beiging). NR induced mitochondrial biogenesis and the expression of beige markers (TBX1 and UCP1) in white adipocytes demonstrating that NR can declutch beiging. NR did not induce PARP activity but supported SIRT1 induction, which plays a key role in beiging. NR induced etomoxir-resistant respiration, suggesting increases in the oxidation of carbohydrates, carbohydrate breakdown products, or amino acids. Furthermore, NR boosted oligomycin-resistant respiration corresponding to uncoupled respiration. Enhanced etomoxir and oligomycin-resistant respiration were dependent on mitochondrial reactive-species production. Taken together, NR supplementation can induce beiging and uncoupled respiration, which are beneficial for combatting metabolic diseases.